Hakikat Ilmu Pengetahuan dalam Perspektif Filsafat Sains - Irda Djesra Mukhdalifa; Nurasiah Nurasiah (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2026)
The nature of knowledge is a fundamental topic in the philosophy of science that examines the origin of knowledge, the process of acquiring it, the validity of scientific truth, and the value and function of knowledge in human life. The rapid advancement of science highlights the need for a philosophical understanding to ensure that scientific development remains grounded in rational, objective, and ethical principles. This study aims to analyze the nature of knowledge from the perspective of the philosophy of science and to explain the interrelationship between ontology, epistemology, and axiology in the construction of scientific knowledge. The research employed a literature review method by examining relevant books, scholarly articles, and other academic sources related to the philosophy of science and the development of knowledge. The findings indicate that knowledge is not merely a collection of facts but the result of a critical thinking process based on scientific methods and rational justification. Furthermore, ontology, epistemology, and axiology constitute three interconnected pillars that shape scientific knowledge into a systematic, objective, and socially beneficial body of knowledge. The study implies that a sound understanding of the philosophy of science is essential for advancing scientific inquiry, improving research quality, and supporting ethical and human-centered decision-making.